Effect of cracking and randomness of inputs on corrosion initiation of reinforced concrete bridge decks exposed to chlorides - P. Konecny; P. Lehner (Fracture and Structural Integrity)
The paper is aimed at the indicative evaluation of the effect of random scatter of input parameters in case of durability of reinforced concrete bridge deck. The time to onset of corrosion of steel reinforcement of concrete bridge deck exposed to chloride is evaluated. The effect of cracking in concrete onto chloride ingress is considered. The selected steel reinforcement protection strategies are: unprotected steel reinforcement, epoxy-coated steel reinforcement and water-proof barrier bellow asphalt overlay. The preliminary model for damage effect on chloride ion ingress through water proof membrane under penetrable asphalt overlay is used. 2-D finite element chloride ingress model is combined with Monte Carlo simulation technique. The innovative crack effect modeling via highly penetrable elements is applied. Deterministic and probabilistic calculations are compared.